Increasing Trend of Caesarean Section in Patan Hospital - Pradhan, Binita; Shrestha, Sarda Duwal; RC, Laxmi; Sharma, Paban; Bhandary, Shital (Journal of General Practice and Emergency Medicine of Nepal, 2015)
Introduction: Caesarean section has been in rising trend every day by day. The study was done to find out the rate of caesarean section and its indications.Methods: This was a retrospective study conducted from January 2010 to December 2014. All cases were reviewed through the records regarding the indications of caesarean section.Results: Out of 44713 deliveries, 18718(41.9%) had caesarean section. The rate of caesarean section was 38.4% in 2010 which increased to 46.9% in 2014. The most common indication for caesarean section was cephalo-pelvic disproportion (19.9%).The next common indication was previous caesarean section (16.5%).Conclusion: The study concluded that there is an increasing trend of caesarean section due to various causes.